The adventurer's son [compact disc, unabridged] : a memoir - Dial, Roman (Harper Audio, 2020)
In the tradition of Into the Wild comes an instant classic of outdoor literature, a riveting work of uncommon depth. I'm planning on doing 4 days in the jungle. It should be difficult to get lost forever: These were the haunting last words legendary adventurer Roman Dial received from his son before the 27-year old disappeared into the jungles of Costa Rica. This is Dial's intensely gripping and deeply moving account of his two-year quest to unravel the mystery of his son's fate.